Understanding the trends of public spending on health sector: World Health Organization - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2020)
Since the global leaders have adopted the Sustainable Development Goals, major steps have been taken by different nations to attain the goal of universal health coverage. Apart from the various measures which have been tried upon, due emphasis has been given to augment the financial allocation to the health sector and thus expand the reach of health care services. The findings of a recently released report have indicated a hike in the total health spending both in low- & middle-income nations and high-income nations. In the nutshell, it was reported that in excess of 50% and 35% expenditure on health has been through government sector and through out of pocket expenditure respectively. In conclusion, there is an immense need for an augmentation in the government spending on the health sector to minimize the health inequalities and the strengthening of the primary health care.